Identification of artistic materials in paintings and drawings by Raman spectroscopy: some challenges and future outlook. (27th August 2015) - Centeno, Silvia A.
Abstract : The aim of the present article is to highlight publications that illustrate some advances in the application of Raman spectroscopy to investigate materials typically observed in manuscripts, drawings, prints, and paintings in museums' and cultural institutions' collections, and to discuss some of the challenges and future prospects. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : The article highlights publications that illustrate some advances in the application of Raman spectroscopy to investigate materials typically observed in manuscripts, drawings, prints, and paintings in museums' and cultural institutions' collections, and discusses some of the challenges and future prospects.